European experience with a first totally leadless cardiac resynchronization therapy pacemaker system. Issue 5 (13th December 2020) - Carabelli, Adrien; Jabeur, Mariem; Jacon, Peggy; Rinaldi, Christopher Aldo; Leclercq, Christophe; Rovaris, Giovanni; Arnold, Martin; Venier, Sandrine; Neuzil, Petr; Defaye, Pascal
Abstract: Aims: Totally leadless cardiac resynchronization therapy (CRT) can be delivered with a combination of Micra and WiSE-CRT systems. We describe the technical feasibility and first insights into the safety and efficacy of this combination in European experience. Methods and results: Patients enrolled had indication for both Micra and WiSE-CRT systems because of heart failure related to high burden of pacing by a Micra necessitating system upgrade or inability to implant a conventional CRT system because of infectious or anatomical conditions. The endpoints of the study were technical success of WiSE-CRT implantation with right ventricle-synchonized CRT delivery, acute QRS duration reduction, and freedom from procedure-related major adverse events. All eight WiSE-CRT devices were able to detect the Micra pacing output and to be trained to deliver synchronous LV endocardial pacing. Acute QRS reduction following WiSE-CRT implantation was observed in all eight patients (mean QRS 204.38 ± 30.26 vs. 137.5 ± 24.75 mS, P = 0.012). Seven patients reached 6 months of follow-up. At 6 months after WiSE-CRT implantation, there was a significant increase in LV ejection fraction (28.43 ± 8.01% vs. 39.71 ± 11.89%; P = 0.018) but no evidence of LV reverse remodelling or improvement in New York Heart Association class. Conclusion: The Micra and the WiSE-CRT systems can successfully operate together to deliver total leadless CRT to a patient. Moreover, the WiSE-CRT system provides the only means to upgrade the large population of Micra patients to CRT capability without replacing the Micra. The range of application of this combination could broaden in the future with the upcoming developments of leadless cardiac pacing.